Imprint Cytology in Diagnosing Various Ovarian Lesions: A Retrospective Study in a Tertiary Care Hospital in Visakhapatnam - Yejjala, Akshay Babu; Poruri, Krishnadivya; Molli, Monica; Epari, Kiran Kumar; Raksha, Sudhakar; Behara, Sireesha (Annals of Pathology and Laboratory Medicine, 2025)
Background: Ovarian neoplasms pose a significant health risk for women, often due to their late detection. Swift and accurate diagnosis can be a game-changer. Cytological methods, like imprint cytology, provide a quick, affordable way to diagnose these tumors during surgery. This can greatly influence surgical decisions and even help preserve fertility in younger patients. Materials and Methods: We conducted a retrospective study on 96 cases of ovarian tumors over a span of two years. During surgery, imprint cytology was performed, and the results were later compared with the final histopathological diagnoses. We measured the diagnostic accuracy, sensitivity, and specificity of this cytological technique. Results: Out of the 96 cases, 90 were benign, one was borderline, and five were malignant. The cytological analysis showed an impressive 95% diagnostic accuracy, with sensitivity at 90% and specificity at 94%. There was a notable correlation between positive cytological findings, such as capsular invasion, and tumor type, especially in serous carcinomas. Imprint cytology was not only effective at identifying malignant cells, but also provided more details on tumor architecture. Conclusion: Cytological evaluation is a reliable, swift, and cost-effective method for diagnosing ovarian tumors during surgery. It aligns well with histopathological findings, helping to accurately classify tumors and guide surgical interventions. Using cytological techniques can reduce the need for extensive surgeries and improve patient outcomes.